tìm a thuộc z để A, a^2 + 3a – 2 là bội của a-1 giúp mình với mình đang cần gấp 21/07/2021 Bởi Arianna tìm a thuộc z để A, a^2 + 3a – 2 là bội của a-1 giúp mình với mình đang cần gấp
Đáp án: a∈{−1;0;2;3} Giải thích các bước giải: a2+3a−2=(a2−a)+(4a−4)+2=a(a−1)+4(a−1)+2=(a+4)(a−1)+2a2+3a−2=(a2−a)+(4a−4)+2=a(a−1)+4(a−1)+2=(a+4)(a−1)+2 a2+3a−2a2+3a−2 là bội của a−1a−1 hay (a2+3a−2)⋮(a−1)⇔[(a−1)(a+4)+2]⋮(a−1)(a2+3a−2)⋮(a−1)⇔[(a−1)(a+4)+2]⋮(a−1) Suy ra 2⋮(a−1)⇒ (a−1)∈{±1;±2}⇒ a∈{−1;0;2;3}2⋮(a−1)⇒ (a−1)∈{±1;±2}⇒ a∈{−1;0;2;3} Bình luận
Đáp án: \[a \in \left\{ { – 1;0;2;3} \right\}\] Giải thích các bước giải: Ta có: \(\begin{array}{l}{a^2} + 3a – 2 = \left( {{a^2} – a} \right) + \left( {4a – 4} \right) + 2 = a\left( {a – 1} \right) + 4\left( {a – 1} \right) + 2\\ = \left( {a + 4} \right)\left( {a – 1} \right) + 2\end{array}\) \({a^2} + 3a – 2\) là bội của \(a – 1\) hay \(\left( {{a^2} + 3a – 2} \right) \vdots \left( {a – 1} \right) \Leftrightarrow \left[ {\left( {a – 1} \right)\left( {a + 4} \right) + 2} \right] \vdots \left( {a – 1} \right)\) Suy ra \(\begin{array}{l}2 \vdots \left( {a – 1} \right) \Rightarrow \left( {a – 1} \right) \in \left\{ { \pm 1; \pm 2} \right\}\\ \Rightarrow a \in \left\{ { – 1;0;2;3} \right\}\end{array}\) Bình luận
Đáp án:
a∈{−1;0;2;3}
Giải thích các bước giải:
a2+3a−2=(a2−a)+(4a−4)+2=a(a−1)+4(a−1)+2=(a+4)(a−1)+2a2+3a−2=(a2−a)+(4a−4)+2=a(a−1)+4(a−1)+2=(a+4)(a−1)+2
a2+3a−2a2+3a−2 là bội của a−1a−1 hay (a2+3a−2)⋮(a−1)⇔[(a−1)(a+4)+2]⋮(a−1)(a2+3a−2)⋮(a−1)⇔[(a−1)(a+4)+2]⋮(a−1)
Suy ra 2⋮(a−1)⇒
(a−1)∈{±1;±2}⇒
a∈{−1;0;2;3}2⋮(a−1)⇒
(a−1)∈{±1;±2}⇒
a∈{−1;0;2;3}
Đáp án:
\[a \in \left\{ { – 1;0;2;3} \right\}\]
Giải thích các bước giải:
Ta có:
\(\begin{array}{l}
{a^2} + 3a – 2 = \left( {{a^2} – a} \right) + \left( {4a – 4} \right) + 2 = a\left( {a – 1} \right) + 4\left( {a – 1} \right) + 2\\
= \left( {a + 4} \right)\left( {a – 1} \right) + 2
\end{array}\)
\({a^2} + 3a – 2\) là bội của \(a – 1\) hay \(\left( {{a^2} + 3a – 2} \right) \vdots \left( {a – 1} \right) \Leftrightarrow \left[ {\left( {a – 1} \right)\left( {a + 4} \right) + 2} \right] \vdots \left( {a – 1} \right)\)
Suy ra \(\begin{array}{l}
2 \vdots \left( {a – 1} \right) \Rightarrow \left( {a – 1} \right) \in \left\{ { \pm 1; \pm 2} \right\}\\
\Rightarrow a \in \left\{ { – 1;0;2;3} \right\}
\end{array}\)